Study of Stability and Reactivity of Cyclopolic Acid Compounds and Their Derivatives Using Semi-empirical Methods AM1 and PM3 - Arsyad Arsyad; Haniran Majid; Topan Setiawan; Muhammad Adrian Natsir (Universitas Khairun, 2021)
The semiempirical method is a method that can be selected in computational chemistry. This method can be used to study the stability and reactivity of cyclopolic acid compounds and their derivatives. This method is simple method in optimizing a compound in calculating the parameters possessed by the atom. Cyclopolic acid is an organic compound that can be found in corn and beans. Analysis using two methods on HyperChem Professional application are AM1 and PM3. Analysis Result shows that the total energy and gradient of each compound do not have significant differences in calculations. As in the structure of 2-formyl-3-(hydroxymethyl)-6-methoxy-5-methylterephthalic acid has a total energy of -80608.1868567 (kcal/mol) and a gradient of 0.0898817 (kcal/mol/Ang) with the AM1 method and total energy of -74935.9180118 (kcal/mol) and a gradient of 0.0874369 (kcal/mol/Ang) with the PM3 method. The stable structure is in the structure of the 2-formyl-3-(hydroxymethyl)-6-methoxy-5-methylterephthalic acid based on the calculation of the total energy and gradient. Meanwhile, according to the calculation of the difference between LUMO-HOMO, it has different results. Where according to the calculation of the energy difference between LUMO-HOMO, the most stable compound structure is the structure of 2-formyl-3-(hydroxymethyl)-4-isocyano-6-metoxy-5-methylbenzoic acid but is not reactive. Likewise, the 2-formyl-4-hidroxy-3-(hydroxymethyl)-6-methoxy-5-methylbenzoic acid, 2-formyl-3-(hydroxymethyl)-6-methoxy-5-methyl-4-(oxo-λ6-methyl)benzoic acid and 2-formyl-3-(hydroxymethyl)-6-methoxy-5-methylterephthalic acid are reactive but unstable compound structure.